1998
DOI: 10.1159/000020850
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk of Fetal Loss after the Coelocentesis Procedure Using a Baboon Model

Abstract: Objectives: The aims of this study were to gain some insight with regard to the safety of the coelocentesis procedure and, to determine pH, pCO2, and base excess status of the extracoelomic fluid 40 days after fertilization. Methods: Twenty-eight timed-mated baboons from the breeding colony of the Biological Resource Laboratory at the University of Illinois at Chicago were studied. The initial 19 animals were used to determine the ultrasonographic relations between the different compartments of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…For example, in Greece up to 10% of the population are carriers of ß-thalassaemia and in women carriers of the disease the knowledge of the actual father is crucial. Previous studies have demonstrated that paternity exclusion can be performed with accuracy after CVS [12,13]. The results of this study have shown that the same methods can be used successfully in the DNA extracted from the coelomic cells, from at least 7 weeks of gestation.…”
Section: Discussionmentioning
confidence: 70%
“…For example, in Greece up to 10% of the population are carriers of ß-thalassaemia and in women carriers of the disease the knowledge of the actual father is crucial. Previous studies have demonstrated that paternity exclusion can be performed with accuracy after CVS [12,13]. The results of this study have shown that the same methods can be used successfully in the DNA extracted from the coelomic cells, from at least 7 weeks of gestation.…”
Section: Discussionmentioning
confidence: 70%
“…The risk of a miscarriage related to the test is about 3 per cent [53]. Coelocentesis is a technically simple procedure which uses extracoelomic fluid as a sample, usually for an early prenatal diagnostic technique [54].…”
Section: Cordocentesis and Coelocentesismentioning
confidence: 99%
“…This author reports that the difficulty for the aspiration of coelomic fluid may require an increased number of multiple punctures further compromising the safety. Santolaya-Forgas et al, 100 examining the safety of coelocentesis in baboons, reported that this procedure might be safe for the pregnancy if it is performed at about 40 days of gestation using a 20 G needle and if less than 3 mL of coelomic fluid is aspirated. In another study, Ross et al 99 reported the results of coelocentesis in 107 women and 337 controls, showing that the risk of fetal loss between 7 and 9 weeks of gestation is about 2%, and comparable to the fetal loss following CVS.…”
Section: Samplingmentioning
confidence: 99%